Improving the diagnosis and treatment of hepatobiliary pathology in adolescents with obesity - L.K. Parkhomenko; L.A. Strashok; M.Yu. Isakova; A.V. Yeshchenko; M.A. Khomenko; O.S. Pavlova; T.M. Kvaratskheliya (Zaslavsky O.Yu., 2018)
Background. The prevalence of obesity among adolescents is increasing, and hepatobiliary pathology is often associated with it. Timely diagnosis and treatment of liver pathology, including non-alcoholic fatty liver disease, and biliary pathology prevent the development of severe complications of obesity. The purpose of the study is to evaluate the structural and functional state of the hepatobiliary system using dynamic echography and to optimize treatment of hepatobiliary disorders among adolescents with obesity. Materials and methods. The study involved 27 patients with obesity aged 12-17 years. A clinical, laboratory and instrumental examination were conducted, which included dynamic echography using Chophytol. The therapeutic possibilities of Chophytol were studied. Results. The study shown that increased appetite, abdominal pain and nausea were leading complains among adolescents with obesity. Signs of moderate atherogenic dyslipidemia were found during the biochemical analysis. Signs of steatohepatosis were observed in 88.8 % of patients according to echography data. Hypokinesis of the gallbladder was detected in 92.6 % of cases. In the majority of patients, there was a hypotonic-hypokinetic type of functional disorders of the biliary tract, an increase in the size of the gallbladder. Comprehensive treatment with Chophytol for 1 month has resulted in positive effects: general well-being has improved, dyspepsia and pain syndrome have decreased; in 52.0 % of patients, the size of the liver has decreased, in 32.0 % - the normalization of echogenicity of the liver parenchyma has occurred; in 28.0 % of adolescents, the contractile function of the gallbladder has improved. Conclusions. In the majority of adolescents with obesity, signs of steatohepatosis and hypotonic-hypokinetic type of functional disorders of the biliary tract are determined. Dynamic echography using Chophytol allows evaluating the function of both the gallbladder and the sphincter apparatus. The application of Chophytol in the comprehensive therapy among obese adolescents with signs of steatohepatosis and with hypokinetic type of functional disorders of the biliary tract is well-founded.